Cover Feature: Multiprotein Dynamic Combinatorial Chemistry: A Strategy for the Simultaneous Discovery of Subfamily‐Selective Inhibitors for Nucleic Acid Demethylases FTO and ALKBH3 (Chem. Asian J. 19/2018). Issue 19 (14th September 2018) - Das, Mohua; Yang, Tianming; Dong, Jinghua; Prasetya, Fransisca; Xie, Yiming; Wong, Kendra H. Q.; Cheong, Adeline; Woon, Esther C. Y.
Abstract : A multi‐protein differential scanning fluorimetry (DSF) strategy is reported. This strategy uses a thermal tag to exclusively fine‐tune the melting temperature of the target proteins such that their individual melting profiles could be monitored in a single DSF melting analysis. When combined with dynamic combinatorial chemistry, formation of protein–ligand complexes can be detected by shifts in T m of proteins engaged in ligand binding. This strategy led to the simultaneous discovery of selective ligands for two epigenetic enzymes, FTO and ALKBH3. More information can be found in the Full Paper by Esther C. Y. Woon et al. onpage 2854 in Issue 19, 2018 (DOI:10.1002/asia.201800729 ). Graphic design: Rachel Lim Si Hui.